PHYTOCHEMICAL SCREENING AND ANTICANCER ACTIVITY OF HYDROALCOHOLIC EXTRACT OF NAREGAMIA ALATA W&A - abi raami (Journal of Global Pharma Technology, 2017)
Objective:The objective of the study was to evaluate the phytochemical and anti-cancer activity of hydroalcoholic extract of Naregamia alata.Naregamia alata (family Meliaceae) is used by various tribal communities and forest inhabitants for the treatment of a variety of diseases. The leaves and stems, combined with bitters and aromatics, are given in decoction for the treatment of biliousness.  Naregamia alata has been used in traditional medicines in India and in the treatment of rheumatism, itch, malarial and chronic fevers, wounds, anaemia, enlarged spleen, ulcers, vitiated conditions of pitta and vata, halitosis, splenomegaly, scabies, pruritis, dysentery, dyspepsia and catarrh. Methods The hydro alcoholic extracts of Naregamia alata was analysed for the presence of flavonoids, alkaloids, glycosides, steroids, phenols, saponins, terpenoid, cardiac glycosides and tannins according to standard method. Cell lines of  Dalton’s Lymphoma Ascites (DLA), Ehrlich Ascites Carcinoma (EAC)  methods have been used in experimental studies of anticancer activity. In the present study, cell lines induced cancer in mice was used to evaluate the anticancer activity. Results: The results of the present findings were the potential of the selected plant as a resource for the discovery of novel anticancer, agents. Conclusion: In this investigation the various parameters proven that the antitumor activity of hydroalcoholic extracts of Naregamia alata, in DLA and EAC tumor bearing mice.Key words: Naregamia alata, phytochemical screening, anti-cancer.